ANALISIS PEMILIHAN WATER METER (WM) PADA PT. MY INDONESIA DI KOTA BATAM - Irawan, Wawan; Sirait, Ganda (LPPM Universitas Putera Batam, 2021)
This research is the first research conducted in the city of Batam, from the results of calculations analyzed using the method of AHP (Analytical Hierarchy Process) and SAW obtained the value of the criteria weight and sub criteria on the selection of water meter suppliers diii PT. MY. There are 4 criteria that affect the selection of suppliers for the company. The result obtained from weighting criteria and sub krteria using AHP method, namely The First Criterion is quality with a weight as large as 0.515. Then followed by the price cretiria with a weight value of 0.273. Furthermore on the shipping criteria with a total weight of 0.115. The last criterion is a View that weighs 0.061. Based on the results of calculations using the SAW method, it can be weighted results from all criteria and sub-criteria with weight values, in the first rank of Hitek suppliers and 0.957 values, both Pacific suppliers with a value of 0.928, ranked third Indopam suppliers with the last 0.850 artha suppliers with a value of 0.842.